Phenological Predictability Index in BRAHMS: A tool for herbarium-based phenological studies - Proença, C; Filer, D; Lenza, E; Silva, J; Harris, SA (2012)
Phenological Predictability Index (PPI) is a tool for analysing phenological patterns incorporating herbarium data within BRAHMS (Botanical Research and Herbarium Management System). PPI produces a maximum-activity period and associated event predictability index between ∼0 and 1. Simple, monthly random sampling showed the ideal number of unique records (event/month/year) is > 50. PPI correctly predicted the maximum-activity flowering month for seven out of eight species studied in the field, and was positively correlated (R 2= 0.610, p = 0.02) with phenophase length, even using suboptimum numbers of unique records. © 2011 The Authors.